Composite negative pole piece, battery cell and lithium ion battery
By setting the coating of current collector and active substances in the composite negative electrode sheet, the performance factors of graphite material and silicon material are controlled, and the battery expansion problem caused by volume expansion of silicon material is solved, and the battery performance with high energy density, long cycle life and low expansion is achieved.
Patent Information
- Application Number
- CN202311092172.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing high-capacity composite negative electrode sheets expand the battery cell due to the expansion of the volume of silicon material during charging and discharging, which affects the rate performance and storage life of the battery.
By providing a coating of current collector and active substances in the composite negative electrode sheet, the active substances include graphite material and silicon material. The performance factors Q1 and Q2 of graphite material and silicon material meet specific relationships, respectively, and control parameters such as particle size distribution, compaction density and skeleton density to achieve low expansion and high energy density.
The composite negative electrode sheet is achieved in lithium-ion batteries with high energy density, long cycle life, good high-temperature storage performance and low expansion, which improves the battery capacity and storage life.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a composite negative electrode sheet, a battery cell and a lithium-ion battery. Background Art
[0002] Existing high-capacity composite negative electrode plates generally use graphite and high-capacity negative electrode materials (containing silicon) as active materials. The volume expansion effect of graphite and silicon materials will cause the battery cell to lose active lithium due to continuous breathing effect and cycle and storage failure under stress conditions. Related technologies alleviate the volume effect of silicon materials by adding graphite materials or other metal particles with small expansion coefficients to negative electrode plates. Although the addition of graphite can inhibit the increase in interface impedance and the pulverization of the plate caused by the volume change of silicon materials during charging and discharging to a certain extent, the specific capacity of graphite materials is much lower than that of silicon materials. When added in small amounts, the effect of inhibiting the cycle cracking and pulverization of silicon negative electrode plates is not obvious. When the amount added is too much, it not only affects the battery energy density, but also increases the thickness of the plate, resulting in the length of the lithium ion transmission path, which will make the battery rate performance worse; at the same time, alloy materials also have the defects of large volume change and low quality advantage. Summary of the invention
[0003] In view of this, the main purpose of the present application is to provide a composite negative electrode plate, a battery cell and a lithium-ion battery. The electrode made from the composite negative electrode plate has the advantages of high energy density, long cycle, good high-temperature storage performance and low expansion.
[0004] To achieve the above-mentioned invention object, the first aspect of the present application provides a composite negative electrode sheet, comprising: a current collector and a coating containing an active material disposed on the surface of the current collector, wherein the active material comprises a graphite material and a silicon material; the performance factor of the graphite material in the active material is expressed as Q1, and the performance factor of the silicon material is expressed as Q2, and Q1 and Q2 respectively satisfy the following relationship:
[0005] Q1=(Dv90-Dv10) / Dn50*OI*PD / TD;
[0006] Q2=(Dv90-Dv10) / Dn50*CS*PD / TD, and 5≤Q1≤15, 3≤Q2≤15;
[0007] Among them, Dv10 and Dv90 are the particle size values of the powder corresponding to the volume percentage of the graphite material or the silicon material reaching 10% and 90%, respectively, Dn50 is the particle size of the powder with a number distribution accounting for 50% in the graphite material or the silicon material, OI represents the orientation degree of graphite in the pole piece, CS represents the silicon grain size in the silicon material, TD represents the skeleton density of the pole piece, and PD represents the compaction density of the pole piece.
[0008] Furthermore, in the graphite material or silicon material, Dv10 is in the range of 0.5 to 10 μm, Dv90 is in the range of 8 to 27 μm, Dn50 is in the range of 0.1 to 17 μm, OI is in the range of 1 to 30, and PD is in the range of 1 to 1.8 g / cm 3 In the range of TD, 1.5~2.5g / cm 3 In the range, CS is in the range of 0.1 to 20 nm.
[0009] Furthermore, the particle size Dv10 of the graphite material is 5 to 10 μm, Dv90 is 15 to 27 μm, and Dn 50 is 1 to 11 μm.
[0010] Furthermore, in the negative electrode sheet, 5≤OI≤15, 1.3≤PD≤1.7g / cm 3 , 1.6≤TD≤2.3g / cm 3 .
[0011] Furthermore, the particle size Dv10 of the silicon material is 5-10 μm, Dv90 is 15-27 μm, and Dn 50 is 1-11 μm.
[0012] Furthermore, the size CS of the silicon grains of the silicon material satisfies: 1≤CS≤10 nm.
[0013] Furthermore, in the composite negative electrode plate, the mass ratio of silicon material to graphite material in the active material is (0.01-0.3):(0.7-0.99).
[0014] Furthermore, the graphite material is selected from one or more of artificial graphite primary particles, artificial graphite secondary particles, natural graphite and microcrystalline graphite.
[0015] Furthermore, the silicon material is selected from one or more of nano-silicon-carbon composite materials, silicon-oxygen-carbon materials, metal-doped silicon-oxygen materials and porous silicon-carbon materials.
[0016] A second aspect of the present invention provides a battery cell, comprising a separator and a plurality of composite negative electrode sheets provided by the first aspect.
[0017] The third aspect of the present invention provides a lithium-ion battery, comprising a shell and a battery cell, wherein the battery cell is placed in the shell, wherein the battery cell comprises a diaphragm and the composite negative electrode plate provided in the first aspect, and the diaphragm is provided on both sides of each of the plates.
[0018] Compared with the prior art, this application has the following advantages:
[0019] In lithium-ion batteries, the volume expansion of the negative electrode during charging is the main reason for the expansion of the entire battery cell. The negative electrode plate provided in the present application includes a current collector and a coating containing an active substance disposed on the surface of the current collector, wherein the active substance includes a graphite material and a silicon material; the performance factor of the graphite material is Q1=(Dv90-Dv10) / Dn50*OI*PD / TD, the performance factor of the silicon material is Q2=(Dv90-Dv10) / Dn50*CS*PD / TD, and 5≤Q1≤15, 3≤Q2≤15; Based on the above, the present application adopts a material containing a particle size (Dv10, Dv90, Dn50*OI*PD / TD) to obtain a negative electrode plate having a volume expansion of the negative electrode during charging. The parameters of the graphite material and silicon material of the pole piece are limited by the parameters of the compaction density PD, skeleton density TD, graphite orientation OI and silicon grain size CS, among which the particle size distribution width index (Dv90-Dv10) is concerned. A reasonable particle size distribution width can increase the compaction density of the material and improve the energy density; and the Dn50 index is used to further limit the fine powder content of the material. The purpose of limiting the fine powder content is to avoid more side reactions and bring about high-temperature storage and cycle performance degradation; in addition, the introduction of compaction density PD and skeleton density TD can strengthen the coupling factors of the material volume energy density and expansion characteristics on the cycle and storage performance. Under the same skeleton density, the lower the compaction density, the greater the porosity, and the smaller the expansion of the corresponding pole piece. If it is the same material, different skeleton densities indicate that the internal skeleton volume is different, which means that the expansion characteristics are different. The design combined with the compaction density can achieve the application of low expansion and high energy density. In summary, this application defines for the first time the material performance factors Q1 and Q2 of the pole piece that take into account high energy density, long cycle, and high temperature storage indicators.
[0020] Therefore, the electrode made of the composite negative electrode sheet of the graphite material and silicon material containing the above performance factors in the present application has the characteristics of high energy density, long cycle, good high temperature storage performance and low expansion. Its application in batteries is conducive to improving the capacity of the battery and making the battery have the characteristics of long cycle and high storage life. When used in electric vehicles, it can improve the cruising range and the life of the vehicle power battery.
[0021] Other features and advantages of the present application will be described in detail through the following specific embodiments. DETAILED DESCRIPTION
[0022] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0025] In this article, Dv is the particle size distribution of the active substance, which refers to the volume percentage, and Dn is the particle size distribution of the active substance, which refers to the number percentage. Specifically, Dv0, Dv10, Dv50, Dv90, and Dv100 are the particle size values corresponding to 0%, 10%, 50%, 90%, and 100% of the volume percentage of the active substance, respectively. Dn50 is the particle size with a number distribution percentage of 50%. The unit corresponding to the particle size value is μm. SSA stands for specific surface area, and its unit is m 2 / g, TD represents the skeleton density, its unit is g / ml, PD represents the compaction density of the pole piece, its unit is g / cm 3 , OI represents the orientation of graphite on the electrode, which is the peak intensity ratio of XRD test: I(004) / I(110), CS represents the silicon grain size in the silicon-based negative electrode, and its acquisition method is: the Si(111) crystal plane diffraction peak with 2-theta of about 28.4° is calculated using the Scherrer formula. For other parameters not described in detail, refer to the conventional acquisition method of parameters in this field.
[0026] In a first aspect, the present application provides a composite negative electrode sheet, comprising: a current collector and a coating containing an active material disposed on the surface of the current collector, wherein the active material comprises a graphite material and a silicon material; the performance factor of the graphite material in the active material is expressed as Q1, and the performance factor of the silicon material is expressed as Q2, and Q1 and Q2 respectively satisfy the following relationship:
[0027] Q1=(Dv90-Dv10) / Dn50*OI*PD / TD;
[0028] Q2=(Dv90-Dv10) / Dn50*CS*PD / TD, and 5≤Q1≤15, 3≤Q2≤15;
[0029] Among them, Dv10 and Dv90 are the particle size values of the powder corresponding to the volume percentage of the graphite material or the silicon material reaching 10% and 90%, respectively, Dn50 is the particle size of the powder with a number distribution accounting for 50% in the graphite material or the silicon material, OI represents the orientation degree of graphite in the pole piece, CS represents the silicon grain size in the silicon material, TD represents the skeleton density of the pole piece, and PD represents the compaction density of the pole piece.
[0030] Furthermore, in the graphite material or silicon material, Dv10 is in the range of 0.5 to 10 μm, Dv90 is in the range of 8 to 27 μm, Dn50 is in the range of 0.1 to 17 μm, OI is in the range of 1 to 30, and PD is in the range of 1 to 1.8 g / cm 3 In the range of TD, 1.5~2.5g / cm 3In the range, CS is in the range of 0.1 to 20 nm. The range described herein includes the minimum and maximum values of the range.
[0031] Furthermore, the particle size Dv10 of the graphite material is 5 to 10 μm, Dv90 is 15 to 27 μm, and Dn50 is 1 to 11 μm.
[0032] Furthermore, in the negative electrode sheet, 5≤OI≤15, 1.3≤PD≤1.7g / cm 3 , 1.6≤TD≤2.3g / cm 3 .
[0033] Furthermore, the particle size Dv10 of the silicon material is 5 to 10 μm, Dv90 is 15 to 27 μm, and Dn50 is 1 to 11 μm.
[0034] Furthermore, a size CS of silicon grains of the silicon material satisfies 1≤CS≤10 nm.
[0035] In the present application, the material is limited from the perspective of particle size, compacted density, skeleton density, graphite orientation and silicon grain size with reference to the above-mentioned parameter ranges. When the performance factor of the graphite material satisfies 5≤Q1≤15 and the performance factor of the silicon material satisfies 3≤Q2≤15, a battery performance that takes into account high energy density, long cycle and high temperature storage can be achieved.
[0036] Furthermore, in the composite negative electrode sheet, the mass ratio of silicon material to graphite material in the active material is (0.01-0.3): (0.7-0.99). Within the above range, the cycle life of the battery can be high, and the amount of silicon material added should not be too high to avoid excessive expansion.
[0037] Furthermore, the graphite material is selected from one or more of artificial graphite primary particles, artificial graphite secondary particles, natural graphite and microcrystalline graphite.
[0038] Furthermore, the silicon material is selected from one or more of nano-silicon-carbon composite materials, silicon-oxygen-carbon materials, metal-doped silicon-oxygen materials and porous silicon-carbon materials.
[0039] In the present application, the coating further comprises a conductive agent and a binder.
[0040] In some embodiments, the coating includes 90% to 95% by mass of active material, for example, 90%, 91%, 93%, 94% or 95%, etc., and also includes 1% to 2% by mass of conductive agent, for example, 1%, 1.5% or 2%, etc., and 1% to 4.5% by mass of binder, for example, 1%, 2%, 3%, 4% or 4.5%, etc.; the sum of the mass percentages of the active material, conductive agent and binder is 100%.
[0041] In some embodiments, the conductive agent includes but is not limited to one or more of carbon nanotubes, graphene, carbon fiber, carbon black (such as acetylene black, Ketjen black), etc.
[0042] In some embodiments, the binder includes but is not limited to one or more of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, carboxymethyl cellulose (CMC) and sodium alginate.
[0043] Specific examples of polyacrylates include polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, and the like, and specific examples of polyolefins include polypropylene, polyethylene, and the like.
[0044] In some embodiments, the current collector may be a copper foil sheet or an aluminum foil sheet, and the specific specifications may be selected based on the energy density and cost of the battery cell, for example, a thickness of 4.5-6.0 μm.
[0045] In the present application, the coating may be applied on one side of the current collector or on both sides of the current collector.
[0046] In the present application, the coating and forming methods of the coating can refer to the existing technology, for example, a slurry containing an active substance of silicon material, a conductive agent and a binder is set on the surface of the current collector by extrusion coating, and the solidified slurry is rolled in the thickness direction of the current collector to obtain a coating.
[0047] A second aspect of the present application provides a battery cell, comprising a separator and a plurality of composite negative electrode sheets provided in the first aspect.
[0048] The third aspect of the present application provides a lithium-ion battery, comprising a shell and a battery cell, wherein the battery cell is placed in the shell, wherein the battery cell comprises a diaphragm and the composite negative electrode plate provided in the first aspect, and the diaphragm is provided on both sides of each of the plates.
[0049] The above-mentioned diaphragm is made of conventional materials, such as polypropylene film or polyethylene film, and the diaphragm materials on both sides of the pole piece can be the same material or different materials. Among them, the pole piece adopts the composite negative pole piece provided in the first aspect of the present application, so as to have all the advantages of the pole piece in the above-mentioned embodiment.
[0050] The following embodiments are used to illustrate the pole piece of the present application.
[0051] Examples 1-10
[0052] A composite negative electrode plate comprises: a current collector and a coating containing an active material disposed on the surface of the current collector, wherein the active material comprises a graphite material and a silicon material; the performance factors Q1, Q2 and parameters Dv10, Dv90, Dn50, PD, TD, OI / CS, etc. of the graphite material and the silicon material are specifically shown in Table 1.
[0053] Comparative Examples 1-6
[0054] Similar to Example 1, the same graphite material and silicon material are selected; the performance factors Q1, Q2 and parameters Dv10, Dv90, Dn50, PD, TD, OI / CS, etc. of the graphite material and silicon material are specifically shown in Table 1.
[0055] The silicon materials used in Examples 1-10 and Comparative Examples 1-6 are specifically:
[0056] Silicon-carbon material: Porous silicon-carbon material Si / C@C deposited by silane, where @ represents coating, specifically refers to carbon-coated Si / C material.
[0057] High first-efficiency silicon-oxygen materials: materials containing Li or Mg doping modifications, such as carbon-coated Li-SiOx, which is characterized as Li-SiOx@C; carbon-coated Mg-SiOx, which is characterized as Mg-SiOx@C.
[0058] Carbon-coated silicon-oxygen materials: for example, carbon-coated SiOx, which is characterized as SiOx@C.
[0059] Table 1
[0060]
[0061]
[0062]
[0063] The process of preparing the negative electrode sheet in Examples 1-10 and Comparative Examples 1-6 includes:
[0064] The graphite material and silicon material described in Table 1 are mixed with a conductive agent and a binder in a mass ratio of 96:1:3, and the mixed powder is placed in a vacuum mixer, and deionized water is added and stirred to obtain a negative electrode slurry; the negative electrode slurry is coated on the opposite sides of the negative electrode current collector-copper foil, and after drying, rolling and cutting, a negative electrode sheet is obtained, which includes a copper foil and a negative electrode active material layer arranged on the two sides of the copper foil. Among them, the binder is a compound of CMC (carboxymethyl cellulose) and SBR (styrene butadiene rubber), and the conductive agent is carbon black SP (super P).
[0065] The process of preparing the positive electrode sheet is as follows:
[0066] The positive electrode active material - ternary material (LiNi0.8Co0.1Mn0.1), conductive agent (Ketjen black + carbon tube), and binder (PVDF) are mixed in a mass ratio of 96:1.5:2.5, the mixed powder is placed in a vacuum mixer, and the solvent - N-methylpyrrolidone (NMP) is added and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, rolling, and cutting.
[0067] The process of assembling the battery is as follows:
[0068] The above-mentioned negative electrode plate is used as the negative electrode, the above-mentioned positive electrode plate is used as the positive electrode, the separator is a polypropylene separator, the electrolyte adopts a 1:1:1 (volume ratio) mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethanol carbonate (DEC) containing 1 mol / LLiPF6, and 10% fluoroethylene carbonate (FEC) additive is added. The battery is assembled in an air-filled glove box to obtain a laminated lithium battery with a rated capacity of 2Ah.
[0069] The above battery was tested under the following conditions, and the test results are shown in Table 2:
[0070] Test temperature: 25℃
[0071] Test voltage range: 2.5~4.2V
[0072] Cycle expansion increase rate: The percentage increase in thickness of the soft-pack battery at the initial and 80% capacity retention rate
[0073] Normal temperature cycle: 1C ratio is 2A current density, charging adopts constant current and constant voltage process, discharging adopts constant current process
[0074] 60-day high-temperature storage performance: The high temperature is 60°C, and the battery is fully charged at 4.2V and stored for 60 days to perform a 1C capacity recovery rate test.
[0075] Table 2
[0076]
[0077] It can be seen from the data in Table 2 above that the electrodes made from the composite negative electrode sheets of graphite material and silicon material containing performance factors within the scope of this application in Examples 1-10 have the advantages of high energy density, long cycle, high temperature storage performance and low expansion. The composite negative electrode sheets in Comparative Examples 1-6 do not use the performance factors within the scope of this application, and cannot take into account high energy density, long cycle, high temperature storage performance and low expansion at the same time, especially the capacity retention rate after 1500 cycles has decreased to a large extent. In Comparative Example 6, the amount of silicon material added is large, and the degree of expansion is significantly increased.
[0078] Obviously, the above embodiments of the present application are merely examples for clearly illustrating the present application, and are not intended to limit the implementation methods of the present application. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. All obvious changes or modifications derived from the technical solutions of the present application are within the spirit scope covered by the present application.
Claims
1. A composite negative electrode sheet, characterized in that: include: A current collector and a coating containing an active material disposed on the surface of the current collector, wherein the active material comprises a graphite material and a silicon material; the performance factor of the graphite material in the active material is expressed as Q1, and the performance factor of the silicon material is expressed as Q2, and Q1 and Q2 respectively satisfy the following relationship: Q1=(Dv90-Dv10) / Dn50*OI*PD / TD; Q2=(Dv90-Dv10) / Dn50*CS*PD / TD, and 5≤Q1≤15, 3≤Q2≤15; Among them, Dv10 and Dv90 are the particle size values of the powder corresponding to the volume percentage of the graphite material or the silicon material reaching 10% and 90%, respectively, Dn50 is the particle size of the powder with a number distribution accounting for 50% in the graphite material or the silicon material, OI represents the orientation degree of graphite in the pole piece, CS represents the silicon grain size in the silicon material, TD represents the skeleton density of the pole piece, and PD represents the compaction density of the pole piece.
2. The pole piece according to claim 1, characterized in that: In the graphite material or silicon material, Dv10 is in the range of 0.5 to 10 μm, Dv90 is in the range of 8 to 27 μm, Dn50 is in the range of 0.1 to 17 μm, OI is in the range of 1 to 30, and PD is in the range of 1 to 1.8 g / cm 3 In the range of TD, 1.5~2.5g / cm 3 In the range, CS is in the range of 0.1 to 20 nm.
3. The pole piece according to claim 2, characterized in that: The particle size Dv10 of the graphite material is 5-10 μm, Dv90 is 15-27 μm, and Dn 50 is 1-11 μm.
4. The pole piece according to claim 2, characterized in that: In the negative electrode sheet, 5≤OI≤15, 1.3≤PD≤1.7g / cm 3 , 1.6≤TD≤2.3g / cm 3 .
5. The pole piece according to claim 2, characterized in that: The particle size Dv10 of the silicon material is 5 to 10 μm, Dv90 is 15 to 27 μm, and Dn50 is 1 to 11 μm.
6. The pole piece according to claim 2, characterized in that: The silicon grain size CS of the silicon material satisfies: 1≤CS≤10nm.
7. The pole piece according to claim 1, characterized in that: The graphite material is selected from one or more of artificial graphite primary particles, artificial graphite secondary particles, natural graphite and microcrystalline graphite; and / or the silicon material is selected from one or more of nano-silicon-carbon composite materials, silicon-oxygen-carbon materials, metal element-doped silicon-oxygen materials and porous silicon-carbon materials.
8. The pole piece according to any one of claims 1 to 7, characterized in that: In the composite negative electrode plate, the mass ratio of silicon material to graphite material in the active material is (0.01-0.3):(0.7-0.99).
9. A battery cell, characterized in that: It comprises a separator and a plurality of negative electrode sheets as described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It comprises a shell and a battery cell, wherein the battery cell is placed in the shell; wherein the battery cell comprises a diaphragm and a plurality of negative electrode plates as described in any one of claims 1 to 8, and the diaphragm is provided on both sides of each of the electrode plates.